Informative Approach to Bibliography: Premises and Rudiments - Лиров, В.П. (Knygotyra, 1972)
The article deals with the significance of a new informative approach to bibliography. It implies an analysis of bibliographic problems in terms of a wider range arising presently with the development a new complex science e. g. informatics. The following main questions, regarded by the author as supplementary to the traditional book investigation, are discussed in the article.(1) Bibliographical information as a kind of social and scientific-technical information, intended to assist in regulating, systematizing and intensifying the flow of press circulating in society.(2) Means of bibliography as models of retrieval systems of documentary information: their coordinates and parameteres.(3) Kinds of bibliography as systems of a wide class information having their own social function, criteria and literary volume range. Peculiarities of kinds of bibliography as systems of information are discussed an example of national bibliography.In the concluding part of the article the importance of informative treatment of bibliography is emphasized. According to the author this treatment is necessary:a) for a new estimation of bibliographic activity in terms of a wide general scientific aspect. A comparative analysis of the new methods of informatics and traditional bibliographic methods should be helpful to this effect;b) for further mechanization of bibliographic processes and their automatization improvement;c) for creating more precise bibliographic scientific “language”, which would help bibliographers to make contact with mathematicians and engineers.The author’s intention was to raise pressing points the final solution of which is subject to further investigation.